A novel hollow microsphere acting on crystallization, mechanical, and thermal performance of poly(3‐hydroxybutyrate‐co‐4‐hydroxybutyrate). Issue 5 (12th August 2021) - Zhang, Jingfan; Wang, Li; Sun, Jun; Jiang, Shengling; Li, Hongfei; Zhang, Sheng; Yang, Wantai; Gu, Xiaoyu; Qiao, Hu
Abstract: Poly(3‐hydroxybutyrate‐co‐4‐hydroxybutyrate) (P34HB) is a bio‐originated and biodegradable semi‐crystalline polyester. However, wide applications of the P34HB are hampered by its poor mechanical properties and processabilities. Divinylbenzene‐maleic anhydride (DM) copolymer is a rigid hollow microsphere. In this work, 0.5 ~ 2.0 wt% DM was used as a novel nucleation agent in P34HB to improve the crystallization of P34HB in order to enhance its properties. The resulting P34HB was characterized using differential scanning calorimetry for its thermal properties, XRD for its crystalline structures, and mechanical tests for its mechanical properties. We show that DM can effectively promote the crystallization process of the P34HB by acting as nucleation sites. Both mechanical properties and material processibility can be readily enhanced. The study has provided a simple approach to address the limitations that have prevented wide applications of an otherwise promising bio‐based degradable polymeric material. In addition, we expect similar approach can be employed for other degradable materials, such as polylactic acid, poly(butylene succinate), and poly(butyleneadipate‐co‐terephthalate). Abstract : Poly(3‐hydroxybutyrate‐co‐4‐hydroxybutyrate) (P34HB) showed relative low crystallinity, slow crystal rate, and even postcrystallization after processing coming from its inherent molecular structure. Divinylbenzene‐maleic anhydride (DM) copolymer as a rigid hollow microsphere was used as a nucleating agent to enhance the crystallization ability of P34HB. At the presence of DM, crystallinity and crystallization rate of P34HB was improved. Meanwhile, the enhancement of crystallization ability results in more satisfying mechanical and heat resistant properties.